STRATEGIES STRATEGIES FOR CULTIVATING THE ENTREPRENEURIAL SPIRIT OF BLIGO SIDOARJO STATE ELEMENTARY SCHOOL: STRATEGI DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN PESERTA DIDIK SEKOLAH DASAR NEGERI BLIGO SIDOARJO - Orien Maulya Pramesti; Arbiya Magfiroh Rohmi; Muhammad Saleh; Sugeng Hariyadi; Siti Ulfah; Muhammad Yuniar Hakim Sidqi; Ahmad Rizal; Imelda Dian Rahmawati (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the strategies employed by Sekolah Dasar Negeri Bligo Sidoarjo in fostering students' entrepreneurial spirit through a planned, integrated, and sustainable approach. The strategies implemented include the planning, execution, and evaluation of programs based on character education, project-based learning, and entrepreneurial practices such as mini-markets and product exhibitions. The findings show that these programs successfully enhanced students' cognitive, affective, and psychomotor skills while building an entrepreneurial mindset from an early age, including risk-taking and innovation capabilities. However, challenges such as time constraints, limited resources, and teacher training have impacted the program's effectiveness. With synergistic support from schools, parents, and the government, entrepreneurship education at the elementary level has the potential to become an essential foundation in shaping creative, independent, and innovative young generations. This study is also relevant to the objectives of the Sustainable Development Goals (SDGs) in promoting inclusive and sustainable economic growth.